Application of Botany in Abiotic and Biotic Stress Resistances in Crops: a Synthesis - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
It is a matter of great concern that Master in Botany is disappearing in many of the universities in India, thereby the importance is decreasing gradually. Most of the botanists are concentrating on basic research, but there is a great necessity of initiation of applied botany. The basic botany is dominated now by molecular biology.Botanists can contribute directly to crop improvement.